High-throughput PacBio library preparation and sequencing techniques for genomic DNA and TNA - Bentz, Meghan L.; Clines, Cristina; Padilla, Jasmine; Horn, Christopher; Lee, Justin; Sheth, Mili (Frontiers in Genetics, 2025)
PacBio Sequencing is an effective tool for achieving long read lengths to close gaps in whole genome assemblies. Limited information is available for automated, high-throughput library preparation workflows for PacBio sequencing. This paper describes two high throughput methods, one for producing barcoded genomic DNA libraries and one for barcoded cDNA and subsequent library preparation, as well as pooling and sequencing on the Sequel II instrument. Test sequencing was performed on 380 genomic DNA samples, of which 28 (7.4%) failed sequencing and needed to be repeated. Test sequencing was performed on 384 Threose nucleic acid samples of which 0 failed sequencing and 49 (12.8%) had a genome coverage <90%. These methods were used to generate and report results for ∼2,000 genomic DNA and ∼30,000 cDNA genome sequences from clinical specimens in 2023.